HASIL BELAJAR LOMPAT JANGKIT (STUDI EKSPERIMEN PENGARUH GAYA MENGAJAR DAN KOORDINASI TERHADAP HASIL BELAJAR LOMPAT JANGKIT SISWA SMK NEGERI 7 MEDAN) - Rizki Bastanta B. Manalu (Universitas Quality, 2018)
The purpose of this research was to determine the effect of teaching style (Inclusion and Exercise) and coordination to Learning Outcomes Triple Jump. Research was conducted on students of SMK Negeri 7 Medan, this research used treatment by level 2 x 2. The sample consisted of 40 students who were divided into 4 groups, which there 10 students. Analysis data taken by ANOVA and Tukey test continued with the level of significance ɑ = .05.These results indicate that (1) The style of teaching inclusions have a better effect than the teaching styles of exercise on learning outcomes Triple Jump which have high coordination. (2) The style of teaching exercise has a better effect than the inclusion of teaching styles to learning outcomes Triple Jump which has a low coordination.